Dexamethasone plus oseltamivir versus dexamethasone in treatment-naive primary immune thrombocytopenia: a multicentre, randomised, open-label, phase 2 trial. Issue 4 (April 2021) - Sun, Lu; Wang, Juan; Shao, Linlin; Yuan, Chenglu; Zhao, Hongguo; Li, Daqi; Wang, Zhencheng; Han, Panpan; Yu, Yafei; Xu, Miao; Zhao, Hongyu; Qiu, Jihua; et al.
Summary: Background: Primary immune thrombocytopenia is an autoimmune bleeding disorder. Preclinical reports suggest that the sialidase inhibitor oseltamivir induces a platelet response in the treatment of immune thrombocytopenia. This study investigated the activity and safety of dexamethasone plus oseltamivir versus dexamethasone alone as initial treatment in adult patients with primary immune thrombocytopenia. Methods: This multicentre, randomised, open-label, parallel group, phase 2 trial was done in five tertiary medical hospitals in China. Eligible patients were aged 18 years or older with newly diagnosed, treatment-naive primary immune thrombocytopenia. Participants were randomly assigned (1:1), using block randomisation, to receive either dexamethasone (orally at 40 mg per day for 4 days) plus oseltamivir (orally at 75 mg twice a day for 10 days) or dexamethasone monotherapy (orally at 40 mg a day for 4 days). Patients who did not respond to treatment (platelet counts remained <30 × 10 9 cells per L or showed bleeding symptoms by day 10) were given an additional cycle of dexamethasone for 4 days in each group. Patients in the dexamethasone plus oseltamivir group who relapsed (platelet counts reduced again to <30 × 10 9 cells per L) after an initial response were allowed a supplemental course of oseltamivir (75 mg twice a day for 10 days). The coprimary endpoints were 14-day initial overall response and 6-month overall response. Complete response was defined as a platelet count at or above 100 × 10 9 cells per L and an absence of bleeding. Partial response was defined as a platelet count at or above 30 × 10 9 cells per L but less than 100 × 10 9 cells per L and at least a doubling of the baseline platelet count and an absence of bleeding. A response lasting for at least 6 months without any additional primary immune thrombocytopenia-specific intervention was defined as sustained response. All patients who were randomly assigned and received the allocated intervention were included in the modified intention-to-treat population analysis. This study has been completed and is registered with ClinicalTrials.gov, number NCT01965626 . Findings: From Feb 1, 2016, to May 1, 2019, 120 patients were screened for eligibility, of whom 24 were ineligible and excluded, 96 were enrolled and randomly assigned to receive dexamethasone plus oseltamivir (n=47) or dexamethasone (n=49), and 90 were included in the modified intention-to-treat analysis. Six patients did not receive the allocated intervention. Patients in the dexamethasone plus oseltamivir group had a significantly higher initial response rate (37 [86%] of 43 patients) than did those in the dexamethasone group (31 [66%] of 47 patients; odds ratio [OR] 3·18; 95 CI% 1·13–9·23; p=0·030) at day 14. The 6-month sustained response rate in the dexamethasone plus oseltamivir group was also significantly higher than that in the dexamethasone group (23 [53%] vs 14 [30%]; OR 2·17; 95 CI% 1·16–6·13; p=0·032). During the median follow-up of 8 months (IQR 5–14), two of 90 patients discontinued treatment due to serious adverse events (grade 3); one (2%) patient with general oedema in the dexamethasone plus oseltamivir group and one (2%) patient with fever in the dexamethasone group. The most frequently observed adverse events of any grade were fatigue (five [12%] of 43 in the dexamethasone plus oseltamivir group vs eight [17%] of 47 in the dexamethasone group), gastrointestinal reactions (eight [19%] vs three [6%]), insomnia (seven [16%] vs four [9%]), and anxiety (five [12%] vs three [6%]). There were no grade 4 or 5 adverse events and no treatment-related deaths. Interpretation: Dexamethasone plus oseltamivir offers a readily available combination therapy in the management of newly diagnosed primary immune thrombocytopenia. The preliminary activity of this combination warrants further investigation. Multiple cycles of oseltamivir, as a modification of current first-line treatment, might be more effective in maintaining the platelet response. Funding: National Natural Science Foundation of China.